ECONOMIC AND LEGAL PREREQUISITES FOR THE FUNCTIONING OF STARTUPS IN MODERN SOCIETY: ISSUES OF INTERNATIONAL AND NATIONAL LEGAL REGIMES - Viktor Makovii; Rashad Mamedov; Illia Klochko (Baltic Journal of Economic Studies)
The subject of the present study is the conceptual, theoretical, methodological and applied foundations of the legal and economic nature of the functioning of a startup as a form of innovative activity. Methodology. The present study employed a combination of general scientific and special legal methods. The analysis determined the quantitative and qualitative parameters of the organisational, legal and economic principles of determining startups in modern conditions. The synthesis yielded common features inherent in the phenomena of socio-economic and legal nature, which serve as a prerequisite for the functioning of a startup. The employment of a comparative legal methodology has facilitated the identification of both the common and distinctive characteristics inherent in the legal consolidation of a startup within the legislation of individual countries, with due consideration for legal and economic prerequisites. The formal legal method established the necessary foundation for formulating conclusions regarding the effectiveness of the regulatory consolidation of the concept and characteristic features of a startup as an innovative product and a subject of the corresponding organisational and legal form, and outlining the corresponding normative proposals. The purpose of the article is twofold: firstly, to establish the state of determination of a startup as an economic category; and secondly, to highlight the prerequisites for the formation and development of such products in the context of international and national legal regimes. This will be achieved through the study of the legal and economic foundations of the specified phenomenon. The results of the study demonstrated that the economic and legal prerequisites for the functioning of a startup are derived from the innovative essence of such a form of entrepreneurial activity and are projected into the plane of implementation of the corresponding product and the exercise of legal personality of a certain participant in such relations within the framework of both national and international legal regimes. Conclusion. From an economic perspective, a startup is regarded as a technological innovation in the context of entrepreneurial activity. Its primary objective is to ensure the most optimal and effective utilisation of available and accessible resources, which are inherently limited in the modern context. It is evident that the emergence and development of a startup is contingent on a number of economic prerequisites. Primarily, there is a necessity for the effective implementation of the formula "small investments - significant profit". Furthermore, there is the possibility of an intensive transition from small to large-scale projects, and the attraction of additional resources in the form of so-called incubators. A startup is defined as a form of innovative activity, characterised by a distinct operational production cycle and a focus on maximised efficiency (defined as the ratio of costs to benefits received, with a high probability of achieving innovative outcomes in comparison to other forms of such activity). A complex combination of means of achieving the set goal and the probability of forming the defining features of a startup (operationality, resource limitations, novelty, innovation) is the most effective when compared with other forms of innovative activity. For nascent enterprises, the investment procedure is a highly effective mechanism that facilitates exponential growth, albeit at the expense of various sources unrelated to the project's originator and the constituents of the pertinent legal entity, which is the form of its implementation. The contract thus serves as the primary instrument for the execution of the startup's legal personality, which is subject to variation in accordance with the diverse scope of its activities. In the context of economic activity, a startup is synonymous with the legal personality of an individual entrepreneur, a private enterprise, a limited liability company, or, in certain circumstances, a structural unit of a specific business entity. Empirical evidence has demonstrated that the organisational and legal structure of a nascent enterprise is predominantly characterised by one of the recognised forms of business entity, with a particular emphasis placed on those models that impose limitations on the contributions of its stakeholders. Conversely, in instances where the initiation of a project is undertaken within the ambit of a structural unit of a legal entity, the latter may not be applicable to business companies. In order for a startup to function legally, it is necessary to determine the legal status of those involved in this type of innovative activity, in terms of both the nature of the object and ensuring the implementation of their powers, in view of the needs of society and the individual.